Notes on the genus Homoneura from Guizhou, China (Diptera: Lauxaniidae) - Gao, Caixia; Yang, Ding (Zootaxa, 2005)
A review of the genus Homoneura from Guizhou, China is provided, including a key to the species. The following 4 species are described as new to science: Homoneura (Chaetohomoneura) setuligera sp. nov., Homoneura (Homoneura) lii sp. nov., H. (H.) procerula sp. nov. and H. (H.) yangi sp. nov.